Influence of electrospinning parameters on Poly(hydroxybutyrate) electrospun membranes fiber size and distribution - Correia, Daniela M. (2013)
Poly(hydroxybutyrate) (PHB) obtained from sugar cane was dissolved in a blend of chloroform and dimethylformamide (DMF) and electrospun at 40 ºC. By adding DMF to the solution, the electrospinning process for the PHB polymer becomes more stable, allowing complete polymer crystallization during the jet travelling between the tip and the grounded collector. The influence of processing parameters on fiber size and distribution was systematically studied. It was observed that an increase of tip inner diameter promotes a decrease of the fiber average size and a broader distribution. On the other hand, an increase of the electric field and flow rate produces an increase of fiber diameter until a maximum of ~2.0 m, but for electric fields higher than 1.5 kV.cm-1, a decrease of the fiber diameter was observed. Polymer crystalline phase seems to be independent of the processing conditions and a crystallinity degree of 53 % was found. Moreover, thermal degradation of the as-spun membrane occurs in single step degradation with activation energy of 91 kJ/mol. Furthermore, MC-3T3-E1 cell adhesion was not inhibited by the fiber mats preparation, indicating their potential use for biomedical applications.